2003
DOI: 10.1038/sj.bjc.6601202
|View full text |Cite
|
Sign up to set email alerts
|

Glucose transporter-1 (GLUT-1): a potential marker of prognosis in rectal carcinoma?

Abstract: The aim of the study is to evaluate the pattern and level of expression of glucose transporter-1 (GLUT-1) in rectal carcinoma in relation to outcome as a potential surrogate marker of tumour hypoxia. Formalin-fixed tumour sections from 43 patients with rectal carcinoma, who had undergone radical resection with curative intent, were immunohistochemically stained for GLUT-1. A mean of three sections per tumour (range 1 -12) were examined. Each section was semiquantitatively scored; 0, no staining; 1, o10%; 2, 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
69
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 31 publications
7
69
1
Order By: Relevance
“…In OSCC, the percentage of cells showing GLUT-1 immunostaining increased with advancing grade, in agreement with previous studies of colorectal and rectal carcinomas where the percentage of positivity increased with the carcinoma grade (17)(18)(19). GLUT-1 regulates glucose influx into cancer cells, assisting in energy preservation, especially in weakly perfused/hypoxic regions characterized by an inadequate supply of glucose.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In OSCC, the percentage of cells showing GLUT-1 immunostaining increased with advancing grade, in agreement with previous studies of colorectal and rectal carcinomas where the percentage of positivity increased with the carcinoma grade (17)(18)(19). GLUT-1 regulates glucose influx into cancer cells, assisting in energy preservation, especially in weakly perfused/hypoxic regions characterized by an inadequate supply of glucose.…”
Section: Discussionsupporting
confidence: 91%
“…Examination of the glycogen content to establish whether any alterations in glucose uptake are related to tumor-associated changes revealed that glycogen was more abundant in nondividing cells of the superficial layers of benign cervical epithelium. Accordingly, it seems that reduced glycogen levels are significantly associated with increased expression of GLUT-1 as the grade of dysplasia increases (14,17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Glut-1 is over-expressed and predicts poor prognosis in a wide range of tumors including those of the head and neck (Oliver et al, 2004), colorectum (Cooper et al, 2003), breast (Younes et al, 1995), cervix (Airley et al, 2001) and clear cell renal carcinoma (Ozcan et al, 2007). The influence of Glut-1 on prognosis and its use as a biomarker may be a manifestation of tumor hypoxia, and the adaptive upregulation of anaerobic glycolysis that may ultimately promote tumour cell survival.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, Glut1 protein expression confers poor prognosis in a wide range of solid tumors. 11,12 Studies regarding GLUT1 expression in HCC have revealed inconclusive results, and the biological significance of GLUT1 expression in HCC remains unknown. [13][14][15][16][17][18][19] Here, we show that GLUT1 expression is increased in a significant number of HCC cell lines and tissues, and high GLUT1 expression correlates with HCC proliferation and invasiveness.…”
mentioning
confidence: 99%